Impact of chalcopyrite depression by water-borne bacteria in pure and combined mineral systems - Liu, W.; Moran, Chris; Vink, S. (Elsevier, 2013)
There is a general trend towards more responsible water management across the minerals industry. Two important strategies have been implementation of water reuse and sourcing of alternative water supplies that otherwise would have been disposed of, such as treated effluent. Both strategies have been shown to result in increased inorganic and organic loads (including bacteria) in mineral processing, in particular, froth flotation. A number of studies have shown the effect of inorganic water constituents on the performance of flotation. However, far less is known about the impacts and processes associated with organic constituents, particularly bacteria. This study investigated the quantitative relationship between bacterial concentration in flotation water using E. coli as the model bacterium and the flotation performance of chalcopyrite. Flotation tests were carried out to quantify the effect of E. coli cells on the flotation of three chalcopyrite-containing systems of increasing complexity: high-purity chalcopyrite, a simulated ore with controlled gangue, and a porphyry copper-gold ore. The experimental results show that E. coli cells negatively affected the flotation efficiency of chalcopyrite in all three systems. The bacterial cells also negatively affected the flotation efficiency of pyrite in the simulated ore system, and gold in the porphyry ore system. The bacterial cells preferentially attached to pyrite over chalcopyrite in the simulated ore system. Findings in this study contribute to identifying some of the potential risks posed by using bacteria-containing water for flotation, when attempting to improve water efficiency. © 2013 Published by Elsevier B.V.